KEY ASPECTS OF THE INDEPENDENT LEARNING OF STUDENTS OF THE MEDICAL FACULTY - Luchkiv, N. (World of Medicine and Biology, 2016)
This article presents the basic aspects of self-study of medical students, that are most widely used in the theoretical departments of medical schools. We established that independent learning of students is determined by content, methods of training and personal characteristics of individuals. It was proved that properly organized system of self-studying is the key to train highly qualified specialists.
Keywords: basic aspects; methods of training; personal characteristics; qualified specialists